2020
DOI: 10.52547/jibs.6.3.229
|View full text |Cite
|
Sign up to set email alerts
|

New records of the family Ichneumonidae (Hymenoptera, Ichnemonoidea) to the fauna of Iran

Abstract: A BS TRA CT . This study has been carried out to collect and identify Ichneumonidae species from northwestern Iran using Malaise traps during 2014. In total, fifteen species into 6 subfamilies are identified. Four species are recorded for the first time from Iran, i.e. Hoplocryptus melanocephalus (Gravenhorst, 1829), Zoophthorus palpator (Müller, 1776), Exochus erythronotus (Gravenhorst, 1820) and Enicospilus cerebrator Aubert, 1966. The geographical distribution data of the recorded species are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A study in the northwest of Iran revealed that 10 species of this subfamily occur in Ardabil province (Ghafouri . Only Woldstedtius biguttatus (Gravenhorst, 1829), has been reported from East Azarbaijan province (Masnadi-Yazdinejad & Jussila, 2008); and three species, Diplazon laetatorius, D. tetragonus (Thunberg, 1824) and Homotropus nigritarsus (Gravenhorst, 1829) from West Azarbaijan province (Malkeshi and Kheiabani, 1997;Manukyan, 2007;Mohammadi-Khoramabadi et al, 2020) and without any record from Kurdistan province.…”
Section: Introductionmentioning
confidence: 99%
“…A study in the northwest of Iran revealed that 10 species of this subfamily occur in Ardabil province (Ghafouri . Only Woldstedtius biguttatus (Gravenhorst, 1829), has been reported from East Azarbaijan province (Masnadi-Yazdinejad & Jussila, 2008); and three species, Diplazon laetatorius, D. tetragonus (Thunberg, 1824) and Homotropus nigritarsus (Gravenhorst, 1829) from West Azarbaijan province (Malkeshi and Kheiabani, 1997;Manukyan, 2007;Mohammadi-Khoramabadi et al, 2020) and without any record from Kurdistan province.…”
Section: Introductionmentioning
confidence: 99%